2000
DOI: 10.1046/j.1460-9568.2000.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential learning‐stage dependent patterns of c‐Fos protein expression in brain regions during the acquisition and memory consolidation of an operant task in mice

Abstract: The present study analysed the effects of the stage of learning of an appetitive operant conditioning task on the spatial and temporal patterns of c-Fos protein levels in the brain of BALB/c mice. c-Fos levels were assessed by immunohistochemistry at either 60, 120 or 180 min after either the first, the second or the fifth daily training session and compared to sham animals. The results show an increase of c-Fos-positive nuclei in several subcortical and cortical brain regions, 60-min post-acquisition. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 62 publications
5
50
0
1
Order By: Relevance
“…Within the context of this framework, there is evidence that parallels cellular and molecular consolidation processes necessary for gene transcription and protein synthesis after induction of LTP in this region. For example, increased expression of LTP-related immediate early genes (i.e., BDNF, zif268, c-FOS, and JUNB) in dorsal CA1 has been observed within 24 hr after the exposure to learning (Frey et al, 1991;Bertaina-Anglade et al, 2000;Gusev et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of this framework, there is evidence that parallels cellular and molecular consolidation processes necessary for gene transcription and protein synthesis after induction of LTP in this region. For example, increased expression of LTP-related immediate early genes (i.e., BDNF, zif268, c-FOS, and JUNB) in dorsal CA1 has been observed within 24 hr after the exposure to learning (Frey et al, 1991;Bertaina-Anglade et al, 2000;Gusev et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence suggesting the CA1 subregion plays a significant role in intermediate/long-term spatial memory and consolidation, but not short-term acquisition or encoding processes (O'Reilly and McClelland, 1994;Treves and Rolls, 1994;Maren et al, 1997;Bertaina-Anglade et al, 2000;Kesner et al, 2004;Lee and Kesner, 2004a;Remondes and Schuman, 2004;Daumas et al, 2005;Hasselmo, 2005;Sharifzadeh et al, 2006). Encoding of information acquired in a Hebb-Williams maze or in contextual fear conditioning, using a within-days analysis, is impaired by targeted lesions to the CA3 and dentate gyrus (DG) subregions, but not from targeted lesions to the CA1 subregion.…”
Section: Introductionmentioning
confidence: 99%
“…The results are expressed as mean7SEM. In order to control for a nonspecific effect of learning, BrdU-IR cells were also counted (batch 2) within the dorsolateral corner of the subventricular zone [22][23][24][25][26][27][28][29][30][31][32] …”
Section: Quantitative Evaluation Of Peroxidase Stainingmentioning
confidence: 99%
“…In this task, two phases of learning can be distinguished: an early phase during which performance improves rapidly, and a late phase during which asymptotic levels of performance are reached. These two phases seem to involve different brain processes [28][29][30][31] and, consequently, may differentially influence neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on changes in c-fos activity, Vann et al (2000) suggested that RE plays a role in working memory. However, c-fos imaging yields complex and sometimes controversial results (e.g., Aggleton et al 2000;Bertaina-Anglade et al 2000;Jenkins et al 2003;Santin et al 2003), while the precise role of c-fos in memory formation and the underlying mechanisms remain unknown (Herrera and Robertson 1996;Zhang et al 2002). Therefore, we used a conventional (reference memory) watermaze task, known to be sensitive to dysfunction of both the hippocampal and prefrontal systems, with each system mediating different aspects of watermaze learning.…”
Section: Introductionmentioning
confidence: 99%